SWOT ANALYSIS OF RUSSIAN ARCTIC STRATEGY: MILITARY ASPECT - Proroković, Dušan; Filijović, Marko (National interest, 2023)
In this paper, the authors focused on Russia’s military activities in the High North, and the SWOT matrix was used for their analysis. Accordingly, the main goal of the work was to determine the main strengths, weaknesses, opportunities and threats that characterise Russian military engagement in the aforementioned area. The analysis showed that the massive presence of infrastructure and military personnel form the backbone of Russian military power in the mentioned area. Within this context, missile systems (hypersonic and others), which are technologically superior to those possessed by the competition, are of particular importance. The absence of a significant presence of NATO military forces in the given area and the strengthening of military cooperation with the Chinese in the Arctic are a chance for Russia to further strengthen its position.On the other hand, the analysis also showed that Russian military activism in the area around the North Pole is characterised by certain weaknesses. The inconsistency of the development of the military component with the economic, social and other aspects of power projection in the region represents the most important one. Apart from leading to an uneven development of the overall potential in the Russian part of the Arctic and thereby preventing the implementation of an integral strategy, it simultaneously makes it difficult to carry out planning and operational military activities, primarily because it causes the emergance of logistical and other gaps. In addition to the above, the condition of a part of the Russian military equipment is also an obvious weakness. It is not at a satisfactory level, which, among other things, is evidenced by frequent accidents related to this issue. With this in mind, climate change is also a relevant factor. They caused the melting of the ice sheet, which throughout history served as a natural shield of the northern Russian borders. With its disappearance, those borders become more open to attack by potential aggressors, at the same time complicating the protection of the Northern Sea Route.The main threat for Russia, according to the analytical matrix, is the announced expansion of NATO. Namely, if Sweden and Finland join that military alliance, the border between Russia and NATO will double. Given that the two Scandinavian countries were militarily neutral for many years, the Russians had no need to build massive defense capabilities along the dividing line with Finland, nor to significantly protect their strategic installations on the Kola Peninsula from a potential threat that could threaten them from that direction. However, if the circumstances change, Kremlin will face obvious problems. These problems primarily refer to the absence of military infrastructure along the mentioned border, but also to the shortcomings related to civilian capacities in the said area, which directly or indirectly hinder the logistical functioning of the army. Nevertheless, if the circumstances change, Kremlin will face obvious problems. The authors conclude that Kremlin should undertake the uniform development of all Arctic potentials, in order for Russia to maintain its position as the leading nation in the region. Only in this way would protection of borders and security of resources be at an optimal level, both in peacetime and in conditions of armed conflict.
Keywords: Arctic; militarization; strategy; SWOT analysis; Russia